A Rare Entity: Adult Asymptomatic Giant Vallecular Cyst - Mümtaz Taner Torun; Ender Seçkin; Ümit Tuncel; Caner Kılıç; Özalkan Özkan (Case Reports in Otolaryngology)
Background. Cysts in the larynx are rare and generally asymptomatic. However, large cysts in adults can be symptomatic. If they are symptomatic, they typically present with respiratory and feeding difficulties. They are usually benign in terms of pathology. Several surgical techniques may be used for treatment. Case Report. A 56-year-old man presented to our clinic with hoarseness. Routine laryngeal examination revealed a giant mass and the larynx could not be visualized. At magnetic resonance imaging (MRI), a cystic mass originating from the vallecula was detected. There was no pathology at the glottic level. We planned tracheotomy for the airway and endoscopic surgery for excision. The mass was excised using CO2 laser and was reported as benign. Conclusion. An asymptomatic vallecular cyst may cause difficult intubation in any operation. It may also cause respiratory or other complications. Airway management should be led by an ear, nose, and throat surgeon, since tracheotomy may be required. Endoscopic excision with CO2 laser is a good choice for treatment in elective cases. In this report, we discuss the diagnosis and treatment of a patient with an asymptomatic giant vallecular cyst.